OPTIMALISASI MANAJEMEN SUMBER DAYA LAYANAN KESEHATAN MELALUI DIGITALISASI PROSES ADMINISTRASI DAN WORKFLOW - Bahdin Nur Tanjung; Jumadiah Wardati; Agung Eko Puryanto (Yayasan Nusantara Hasana Berdikari, 2024)
This Community Service Program focuses on improving the efficiency and traceability of healthcare services through the digitization of administrative processes and workflows. Common challenges faced by our partners include long wait times, duplicate record-keeping, difficulty tracking files, delays in claims processing and billing, and an unbalanced workload for staff. Interventions are implemented through mapping of current processes, baseline measurements (wait times, turnaround times), design of digital workflows, development of standard operating procedures (SOPs), implementation of electronic forms and queue management systems, and a dashboard for monitoring capacity and workload. Success is measured by reductions in wait times, improved data accuracy, accelerated service processes, and increased staff productivity.